Improving Spiritual Well-Being in Patients with Lung Cancers - Piderman, Katherine M. (J Pastoral Care Counsel, 2015)
Patients with lung cancer report more disease burden and lower spiritual well-being (SWB) compared with other cancer patients. Understanding variables that lessen disease burden and improve SWB is essential. The aim of this study was to explore the relationship between motivational level for physical activity and SWB in patients with lung cancer. Linear regression showed increased SWB as stage of change for physical activity increased (p<0.0001), even after adjusting for multiple demographic variables.